2007
DOI: 10.1016/j.trf.2006.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effectiveness of physical threats in road safety advertising: The role of the third-person effect, gender, and age

Abstract: Threatening advertisements have been widely used in the social marketing of road safety.However, despite their popularity and over five decades of research into the fear-persuasion relationship, an unequivocal answer regarding their effectiveness remains unachieved. More contemporary "fear appeal" research has explored the extent other variables moderate this relationship. In this study, the third-person effect was examined to explore its association with the extent male and female drivers reported intentions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
82
1
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(99 citation statements)
references
References 38 publications
10
82
1
6
Order By: Relevance
“…As predicted (Hypothesis 3), the current study's results supported previous empirical evidence (i.e., Lewis et al, 2007b) with females demonstrating an attenuation of the classic TPE and males demonstrating a classic TPE, for negative appeals of both high and low response efficacy. Thus, similar to the conclusions drawn by Lewis et al, (2007b), the TPE results derived in the current study have significant theoretical and practical implications.…”
Section: Tpe Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…As predicted (Hypothesis 3), the current study's results supported previous empirical evidence (i.e., Lewis et al, 2007b) with females demonstrating an attenuation of the classic TPE and males demonstrating a classic TPE, for negative appeals of both high and low response efficacy. Thus, similar to the conclusions drawn by Lewis et al, (2007b), the TPE results derived in the current study have significant theoretical and practical implications.…”
Section: Tpe Resultssupporting
confidence: 89%
“…Interestingly, whilst meta-analytical evidence has suggested that demographic characteristics such as gender and age have limited or no impact upon the effectiveness of fear appeals (Witte & Allen, 2000), recent evidence, found in relation to gender, has challenged this conclusion (Goldenbeld, Twisk, & Houwing, 2008;Lewis, Watson, & Tay, 2007b). For instance, Lewis et al (2007b) found that males were more likely to report appeals of high physical threats (i.e., appeals which depict death and/or injury as the consequences of unsafe/illegal behaviour) as having more influence on other drivers in general than themselves (the third-person effect [TPE], Davison, 1983;Lewis et al, 2007b). Moreover, males in this study were found to report significantly less intention to improve their future driving behaviour in relation to speeding and drink driving than females (Lewis et al, 2007b).…”
Section: Negative Versus Positive Message-relevant Affect: An Overviementioning
confidence: 99%
See 2 more Smart Citations
“…4 August 2014334 http://dx.doi.org/10.15206/ajpor.2014 likelihood of message influence on the self and those closest (self and family (88%)), and other supporting voters (91%) than on the others (uncertain voters (76%), opposition supporters (78%)). These findings support the earlier research on "reverse" third-person effect or first-person effect, that message desirability plays a key role in persuasion and positive influence on self and others (Duck et al, 1995;Day, 2006;Lewis, Watson & Tay, 2007;Spinda, 2009;Lewis, Watson, & White, 2008). The study indicates that the BN respondents display a high confidence in predicting the influence of the BN political communication devices on self, others, and distant others.…”
Section: Discussion On the Findings Of The Studysupporting
confidence: 88%